A new species of the Didelphid marsupial genus Monodelphis from Eastern Bolivia (2012)
ABSTRACT: A new species of the didelphid marsupial genus Monodelphis is described from the eastern Bolivian province of Santa Cruz. The new species, currently known from a single specimen, belongs to the M. brevicaudata group but differs from other taxa within that clade (M. brevicaudata, M. domestica, M. glirina, M. maraxina, and M. palliolata) in size, qualitative morphological characters, and cytochrome-b gene sequences.